(untitled) (Journal of Applied Learning and Teaching, 2024)
The present study explored teachers’ perspectives on the challenges and benefits of using ChatGPT in language classrooms, adopting an ecological perspective. To do so, ten Iranian language teachers were selected using convenience sampling and completed narrative frames about the use of ChatGPT in language classrooms. Semi-structured interviews were used to explore their beliefs on the impact of integrating ChatGPT in their classes. Employing deductive thematic analysis, the findings were organized into three different layers of educational ecology: microsystem, mesosystem, and macrosystem. The findings revealed that there are challenges and benefits in different layers of the classroom ecosystem regarding using ChatGPT in language classrooms. Teachers and teacher educators can benefit from the findings of the present study by raising their awareness of the implications of ChatGPT in language classrooms and adapting their practices to integrate this AI tool in their teaching practice.